The Reliability of COVID-19 Data in the Shadow of Anti-Pandemic Measures’ Cancellation - Evgeny Sedashov; Mert Moral (Siyasal: Journal of Political Sciences)
COVID-19 pandemic necessitates taking measures that may be very costly from an economic standpoint and likely to make the mass public discontent. If an anti-pandemic regimen does not accomplish its goals, its costs become even harder to justify. We argue that, under such circumstances, cancellation of an anti-pandemic regimen would decrease the reliability of health data because rank-in-file policymakers and bureaucrats have incentives to present more optimistic statistics to signal their competence and politicians would further pressure them to report statistics that appear to agree with the cancellation of restrictions and give legitimacy to taking the measures. Our empirical analyses suggest that closeness to the restrictions’ cancellation date is associated with lower reliability of COVID-19 daily cumulative cases and deaths data. Being robust to several sensitivity and robustness checks, this finding is alarming from the perspective of representative democracy and for those who have to survive in these turbulent times.